PEMBINAAN KARAKTER MENURUT HADIS NABI SAW (Analisis Terhadap Hadis-Hadis Kejujuran) - Tasbih, Tasbih (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2014)
Character Development becomes great concern of Prophet Muhammad which is defined as a statement: I was raised to improve the morals . He tried to instill a prophetic character, one of them is honesty. An important point of the construction of Prophet Muhammad’s are a gradual and consistent. Development is done more emphasis on attitude exemplifies. People who want a good character must make the Prophet as his role model. His exemplary application that he suggest are always honest in every speech and actions because honesty is an absolute requirements the establishment of the good character.